Assessment of post-LASIK flap thickness created by mechanical microkeratomes by anterior segment optical coherence tomography - Islam A.M Amr; Hassan S.E Yousef; Asaad N Ahmed (Wolters Kluwer Medknow Publications, 2022)
Background and aim Laser-assisted in situ keratomileusis (LASIK) is the most popular refractive surgical operation for the correction of myopia, hyperopia, and astigmatism. Corneal flap creation is an essential step for the success of LASIK. The aim of the work is to evaluate the accuracy of the post-LASIK flap thickness created by mechanical microkeratomes using Anterior segment optical coherence tomography (ASOCT). Patients and methods This study included 60 eyes (of 30 patients), who underwent LASIK for refractive error correction. The patients were divided into two groups: (a) group A involved 30 eyes of 15 patients; in this group, the mechanical microkeratome Moria M2 (Moria M2, 110) was used. (b) Group B involved 30 eyes of 15 patients; in this group, the microkeratome Moria M2 (Moria M2, 100 with medlogic plano head) was used. Results As regards postoperative changes in flap thickness, the results of the current study showed that there were no considerable changes in thickness of the flap between 1 week, 1 month, 3 months, and 6 months postoperatively in either group. Conclusion Moria M2 100 with medlogic plano head created LASIK flaps with thinner thickness, and more predictability and more preservation of bed thickness than those created with the Moria M2 110.